Maternal and perinatal outcome in patients of preeclampsia with and without HELLP syndrome - Madge, Hritul; Seth, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is seen in about 5-10% of all pregnancies and HELLP Syndrome occurs in 6-12% of these patients. Both are known to increase maternal and perinatal morbidity. The study aims to provide a comprehensive view of these myriad outcomes in the mother and neonate both, in each of the groups. It also compares the incidence of such outcomes in mother and child, in preeclampsia only and in those complicated by HELLP syndrome. Methods: This prospective, observational, comparative study was conducted at a tertiary referral centre. 55 patients with preeclampsia were compared with 55 patients with HELLP syndrome. The relevant clinical features, laboratory investigations and the maternal and perinatal outcomes along with the incidence were studied and results analyzed. Results: Significant differences were observed in laboratory parameters and duration of ICU stay in patients with preeclampsia and patients with HELLP syndrome. Incidence of maternal complications and need for blood transfusion was greater in HELLP syndrome. Only marginal differences were observed in birth weight, NICU admission rates and neonatal mortality rates. Conclusions: HELLP syndrome is associated with increased maternal morbidity and mortality as compared to preeclampsia. Neonatal outcomes appear to be influenced; only marginally, by HELLP syndrome, nevertheless, their incidence is more than in preeclampsia. Aggressive treatment for pregnant women appears to decrease the maternal mortality rate.